Programa nutricional entre atletas competitivos : perfil e mudanças alimentares após aconselhamento nutricional - Nascimento, Marcus Vinicius Santos do (2015)
The Bolsa Atleta program is the biggest athletes sponsorship program, however no study evaluated the dietary intake these athletes. This study was divided into two stages. The first aimed to compare the eating habits and the dietary intake of male and female athletes, while the second evaluated the effect of a nutrition intervention on body composition, nutritional intake, nutrition knowledge and dietary habits of athletes. Eighty athletes participated in the first stage of the study, being 47 male and 33 female. A 24-hour recall was applied to evaluate athletes dietary intake. Both groups showed a high inadequacy in caloric intake. Men were more inadequate in protein and saturated fat intake, while women showed a higher percentage of inadequacy in monounsaturated fat. Both groups showed a high inadequacy in vitamin A, E, D and calcium intake. Men were more inadequate in vitamin C and sodium, while women had a higher inadequacy in vitamin B12, B3, magnesium, folate, phosphorus, and five times more probability of inadequate iron intake. Women had a more inadequate intake of fruit, meat, and Low adequacy of pre and post workout meals. Athletes of both sexes present inadequacies on dietary intake, however, these were higher among women.In the second stage of the study, 32 athletes, 21 adults and 11 adolescents received nutritional counseling and were analyzed separately. After follow-up, both groups had increased body mass and lean mass and adolescents increased arm muscle area. There was an increase in the number of meals and reduction in the range and the omission of the them in adolescents. Both groups increased the adequacy of pre and post workout meals and nutrition knowledge. Teenagers increased their water intake after the intervention. Both groups showed a high prevalence of positive effects on energy intake, nutrients and food portions. The nutritional counselling has been effective in promoting beneficial changes on the athlete´s nutritional knowledge, their body composition, and their dietary intake, however, the overall effect was greater in the adolescents than in the adults.